Eleanor Vadala with Gammacell 220 at the Naval Air Material Center - United States. Navy (1958)
Eleanor Vadala, chemist, demonstrating use of the Gammacell 220, a textile chemistry machine, at the Naval Air Material Center's Aerospace Materials Laboratory. The Gammacell 220 is a source of Cobalt-60 gamma radiation, which is commonly used to alter the physical properties of textile fibers and polymers.
Keywords: Women in science; Aerospace Research Laboratories (U.S.); Employees; Textile machinery; Radiation; Machinery; Naval Air Engineering Center (U.S.); Cobalt--Isotopes; Women employees; Women chemists; Chemists; Vadala, Eleanor, 1923-